Managing Behavior Based on Character in The Era Of Globalization - Heriyadi Heriyadi (Journal of Research in Educational Management, 2023)
Character education management is to shape one's personality through character education. The results are seen in a person's real actions, namely good behavior, honesty, responsibility, respect for the rights of others, hard work, empathy, and so on. This research aims to learn about the management of student character education in responding to the challenges of modernity in the era of globalization at schools based on pesantren. This research uses a qualitative method with a case study type with a case study design. The case study in this research is an in-depth study of individuals, a group, an organization, an activity program, and so on at a certain time. Data collection techniques in this study were carried out circularly using three approaches: l) participant observation, 2) in-depth interviews, and 3) documentation. While the data analysis in this study was carried out through; data reduction, data presentation, and drawing conclusions or verification. Findings about the management of student character education in responding to the challenges of modernity in the era of globalization at schools based on pesantren include; 1) the planning of the student character education management program at schools based on pesantren is to plan the formation of the vision and mission according to the goals of the foundation, after that, design the formation of the structure and determine the main tasks and functions, plan the budgeting of program needs and plan the arrangement of the program by student character education. 2) The implementation of the student character education management program at schools based on pesantren is carrying out the vision and mission listed in positive value habits and three methods, namely understanding, habits, and exemplary by character education; members of the institution are responsible and work according to their duties and authorities, provide needs by the school program and carry out program arrangements that are carried out together.